_ _: _ - Broz, Pavel; Windrichova, Jindra; Fuchsova, Radka; Topolcan, Ondrej; Pecen, Ladislav; Mayer, Otto; Kucera, Radek (Journal of Medical Biochemistry, 2020)
Aim: To compare four automated immunoassays for the measurement of vit25OHD and to assess the impact on the results obtained from a healthy population.Methods: We analysed 100 serum samples on Unicel DxI 800 (Beckman Coulter), Architect i1000 (Abbott), Cobas e411 (Roche) and Liaison XL (DiaSorin). A Wilcoxon signed-rank test was used to compare the different methods’ values and method comparison was further performed using Spearman’s rank correlation, as well as linear and Passing-Bablok regression.  In order to clinically categorise the obtained values, results were categorised into the following groups: 0–25 nmol/l, 25–50 nmol/l, 50–75 nmol/l and above 75 nmol/l and compared. The percentage of samples below 75 nmol/l and below 50 nmol/l was then calculated for every method.Results: According to paired comparisons, each method differs from others (P
Keywords: _